Isotopic Evidence for Camelid Husbandry During the Formative Period at the Pacopampa Site, Peru. (2nd July 2020) - Takigami, Mai; Uzawa, K.; Seki, Y.; Chocano, D. Morales; Yoneda, M.
ABSTRACT: Camelids were domesticated in the Andean highlands, such as in the puna habitat, and dispersed into lowland areas and the northern Central Andes. As camelids domesticated in a particular region would have had a greater economic benefit than visiting- or hunted wild camelids, it is important to reconstruct the dispersal of camelid husbandry from its initial site throughout the ancient Andean civilisation. We carried out multi-isotope analyses of animal remains recovered from the Pacopampa site to investigate the nature of camelid pastoralism and utilisation. Strontium and oxygen isotope ratios from tooth enamel suggested that camelids in the early Late Formative Period (800–500 BC) were born near the site and remained in the same habitat for up to three years. Although corresponding data for the Middle Formative Period (1200–800 BC) were not available, carbon and nitrogen isotope ratios were statistically different from those of the Late Formative Period, supporting the possibility that the camelids inhabited the highland plateau like puna . It is inferred that in the northern highlands camelids were initially rare and regarded as either tribute or ritual animals, or they were used as pack animals. Camelid husbandry using maize as fodder began during the Late Formative Period at Pacopampa.